Study on Growth Process of Ag(In, Ga)Se2 Films by a Three-Stage Co-Evaporation Method Using Molecular Beam Epitaxy Apparatus - Xianfeng Zhang; Masakazu Kobayashi (IEEE Photonics Journal)
Ag(In, Ga)Se2 (AIGS) has been considered as a promising candidate material for the top cell of chalcopyrite-based tandem solar cells. In this work, the process of (AIGS) film growth by a three-stage molecular beam epitaxy method is studied. The diffusion of silver and grain growth of AIGS films from the first stage-deposited (In, Ga)2Se3 is investigated. Energy dispersive spectroscopy mapping is used to reveal the distribution of silver in the film during each stage of the deposition process. A sharp silver accumulation at the surface of the film at the early stage of the deposition process is observed. This has led to the formation of a silver-rich phase, which gradually diffused into the film to produce a homogeneous distribution. X-ray diffraction results illustrate the phase changes of AIGS films. Based on the result, a growth model for AIGS films from the first stage to the second stage is suggested as (In, Ga)2Se3 → Ag9 (In, Ga)Se6 at the surface and (In, Ga)2Se3 at the bottom of the film → silver-rich AIGS film. During the third stage, the silver-rich film was converted to silver-poor film. The performance of AIGS solar cells fabricated from various samples was compared, and a highest efficiency of 7.1% was obtained.